Post a New Question

Math

posted by on .

Is the derivative of (squarerootof x)/(3x+1) : 3x+1-3squarerootofx/(2squarerootofx)(3x+1)^2

  • Math - ,

    y = √x/(3x+1)

    y' = (1/2√x (3x+1) - √x (3)) / (3x+1)^2
    = (3x+1) - 2√x√x(3)) / 2√x (3x+1)^2
    = (1-3x) / 2√x (3x+1)^2

    Looks like you forgot a factor of √x:

    y = u/v
    y' = (u'v - uv')/v^2

  • Math - ,

    also ,my own typing was sloppy.

    y' = (1/(2√x) (3x+1) - √x (3)) / (3x+1)^2

    Looks like you forgot to put the numerator over a common denominator of 2√x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question